Genetic and environmental effects on milk yield of Pitangueiras cattle - Lôbo, R. B.; Duarte, F. A.M.; Gonçalves, A. A.M.; Oliveira, J. A. [UNESP]; Wilcox, C. J. (Cambridge University Press (CUP), 1984)
Data from 5270 lactation records of 1380 cows sired by 132 bulls and recorded from 1962 to 1977 were analysed. Statistical analyses, using least squares and maximum likelihood methods, showed significant effects for genetic group, age of cow, month and year of calving, and lactation length. Overall mean milk yield was 2780 kg (CV = 0·31) with mean lactation length of 281 days. Maximum production occurred in the fifth lactation (104 or 105 months of age at calving) with a yield of 1·3 times that of the first lactation. Repeatability estimated by intraclass correlation was 0·40 (s.e. 0·03). Heritability estimated from paternal half-sib correlation was 0·16 (s.e. 0·06). Overall results were very similar to those obtained from research with European breeds in temperate areas. © 1984, British Society of Animal Science. All rights reserved.